2019
DOI: 10.4236/ojo.2019.94010
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Positioning of a Clavicle Hook Plate Is a Risk Factor for Acromial Fractures after Acromioclavicular Joint Dislocation

Abstract: Purpose: Acromioclavicular (AC) joint dislocation is commonly treated using a clavicle hook plate (HP). However, previous reports have indicated that acromial fractures may occur after HP fixation. The purpose of this study was to identify risk factors for acromial fractures. Methods: A retrospective study was conducted on 39 patients with AC joint dislocation who were treated using clavicle HP fixation in our hospital between 2006 and 2017. Related parameters, including Rockwood classification, hook angle, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Kim et al 22 used 3DCT to analyze the changing position of the acromioclavicular joint and clavicle after hook plate surgery and reported that a mismatch between the center of rotation of the clavicle and the rotational axis of the hook plate resulted in stress at the undersurface of the acromion. Using plain radiography, Tamiya et al 23 showed that a posterior hook position exacerbated bone erosion and posed a risk of acromion fracture. Using CT, the present study investigated patients after CHP fixation and found that posterior hook placement tended to be associated with deep bone erosion and increased the likelihood of complications (see Figure , Supplemental Digital Contents 4A , http://links.lww.com/JOT/B617).…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al 22 used 3DCT to analyze the changing position of the acromioclavicular joint and clavicle after hook plate surgery and reported that a mismatch between the center of rotation of the clavicle and the rotational axis of the hook plate resulted in stress at the undersurface of the acromion. Using plain radiography, Tamiya et al 23 showed that a posterior hook position exacerbated bone erosion and posed a risk of acromion fracture. Using CT, the present study investigated patients after CHP fixation and found that posterior hook placement tended to be associated with deep bone erosion and increased the likelihood of complications (see Figure , Supplemental Digital Contents 4A , http://links.lww.com/JOT/B617).…”
Section: Discussionmentioning
confidence: 99%
“…Pressure is continuously applied to the undersurface of the acromion after the operation to suppress the upward dislocation of the distal end of the clavicle, and this pressure has been shown to cause subacromial osteolysis [2][3][4][6][7][8][9][10]. If the severity of subacromial osteolysis progresses significantly, a serious complication, acromial fracture, occurs [12][13][14]. There is a report recommending the locking plate because the complication rate of the clavicle hook plate is higher than that of the locking plate [15][16][17].…”
Section: Introductionmentioning
confidence: 99%